Suppression of m6A reader Ythdf2 promotes hematopoietic stem cell expansion. Issue 9 (September 2018) - Li, Zhenrui; Qian, Pengxu; Shao, Wanqing; Shi, Hailing; He, Xi; Gogol, Madelaine; Yu, Zulin; Wang, Yongfu; Qi, Meijie; Zhu, Yunfei; Perry, John; Zhang, Kai; et al.
Abstract Transplantation of hematopoietic stem cells (HSCs) from human umbilical cord blood (hUCB) holds great promise for treating a broad spectrum of hematological disorders including cancer. However, the limited number of HSCs in a single hUCB unit restricts its widespread use. Although extensive efforts have led to multiple methods for ex vivo expansion of human HSCs by targeting single molecules or pathways, it remains unknown whether it is possible to simultaneously manipulate the large number of targets essential for stem cell self-renewal. Recent studies indicate thatN 6 -methyladenosine (m6 A) modulates the expression of a group of mRNAs critical for stem cell-fate determination by influencing their stability. Among several m6 A readers, YTHDF2 is recognized as promoting targeted mRNA decay. However, the physiological functions of YTHDF2 in adult stem cells are unknown. Here we show that following the conditional knockout (KO) of mouseYthdf2 the numbers of functional HSC were increased without skewing lineage differentiation or leading to hematopoietic malignancies. Furthermore, knockdown (KD) of humanYTHDF2 led to more than a 10-fold increase in the ex vivo expansion of hUCB HSCs, a fivefold increase in colony-forming units (CFUs), and more than an eightfold increase in functional hUCB HSCs in the secondary serial of a limiting dilution transplantation assay. Mapping of m6 A in RNAs from mouse hematopoietic stem and progenitor cells (HSPCs) as well as from hUCB HSCs revealed its enrichment in mRNAs encoding transcription factors critical for stem cell self-renewal. These m6 A-marked mRNAs were recognized by Ythdf2 and underwent decay. InYthdf2 KO HSPCs andYTHDF2 KD hUCB HSCs, these mRNAs were stabilized, facilitating HSC expansion. Knocking down one of YTHDF2′s key targets, Tal1 mRNA, partially rescued the phenotype. Our study provides the first demonstration of the function of YTHDF2 in adult stem cell maintenance and identifies its important role in regulating HSC ex vivo expansion by regulating the stability of multiple mRNAs critical for HSC self-renewal, thus identifying potential for future clinical applications.